Awareness and acceptability of the usefulness and products of jatropha curcas (L.) plant in Kano State, Nigeria (2013)
Inadequate alternative sources of energy and low income engender unsustainable exploitation of the environment by the inhabitants of semi arid regions. Literature abounds on the potentials of Jatropha curcas as an alternative source of energy. This study reports the awareness and acceptability of the energy and other potentials of J. curcas in Kano state. Primary data were collected using FGDs and a set of structured questionnaire administered randomly on 1280 farmers. Information were sought on level of awareness about J. curcas, proportion of farmland available for its planting, level of acceptability of its products, government incentives and consent to utilize J. curcas and substitute petroleum diesel with J. curcas biodiesel. Data was analyzed using descriptive statistics and logit regression at p = 0.05. The usefulness of J. curcas for farmland boundary (100.0%) and homestead planting (98.48%) were more popular while its use as live fence was the most (99.24%) acceptable among the respondents. Also, 68.18% of the respondents accepted Jatropha oil while 90.91% accepted its biodiesel. About 83.3% of the farmers had less than a quarter of their farmlands planted with J. curcas. However, if market outlet and incentives were to be provided by the government, 30.0% and 55.0% of the respondents respectively, indicated willingness to commit the whole and half of their farmlands to J. curcas plant production. Awareness of J. curcas is likely to influence knowledge on the importance J. curcas seed cake (odds ratio = 4.44) in Kano state. So also, its awareness will likely influence the willingness to use J. curcas oil (odds ratio = 2.34), its seed cake (odds ratio = 4.4) and biodiesel (odds ratio = 4.37). Awareness of J. curcas plant usefulness but not that of its products is very high in Kano State. Deliberate promotion of the plant products in addition to establishment of a Jatropha System for sustainability of its production among farmers is therefore recommended.